If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-1)+5=32
We simplify the equation to the form, which is simple to understand
3(2x-1)+5=32
Reorder the terms in parentheses
+(+6x-3)+5=32
Remove unnecessary parentheses
+6x-3+5=+32
We move all terms containing x to the left and all other terms to the right.
+6x=+32+3-5
We simplify left and right side of the equation.
+6x=+30
We divide both sides of the equation by 6 to get x.
x=5
| 5=1+2x | | 24x-7-16x+3=23x-8-15x+13 | | 4x-2(x-3)=x+12 | | 7(p+2)-4p=3p+14 | | 100y+300x*40=8400 | | 7/9*1/5*3/35 | | -1/6-6 | | -2/9*-1/4 | | [3+4x]=15 | | 100+300*40=8400 | | 21/1575 | | 2(v-3)-7=-3(-5v+1)-5u | | C/6=4 | | -4(-5w+6)-7w=5(w-5)-9 | | 2n+10=107.50 | | (-2/4)x+3=1 | | 142+2.7x=300 | | 7(n-2)-6=2n+8+n | | 900x=10 | | 2(x-.5)-6x= | | 142+2.7x=40 | | x+5-8=-2 | | -5(2w-6)+w=3(w+8) | | 3000x-6000(x+0.3)=93 | | 1=(-w+6) | | w(4-w^2)=8-w^2 | | [x-8]=11 | | 7(u+2)=42 | | 18x+4/17-17x=1/3 | | -3x-2(8+5x)=14-5(2x-5) | | 6(x+3)-10=-2(x-4) | | x+(-12)=13 |